LEVELS’ INFLUENCE OF IFN-γ AND IL-10 IN CHILDREN WITH EPILEPTICUS STATUS - Salim, Irfan Agus; Muid, Masdar; Sujuti, Hidayat (Malang Neurology Journal, 2018)
Background. Seizures are a common clinical manifestation in the emergency room. Nearly 5% of children aged under 16 years. Seizures are important as a sign of neurological disorders. Members of interferon are widely studied with seizures and epileptogenesis is interferon-γ. In a study by Choi in 2011, a study of seizures in humans showed that the condition of status epilepticus increased levels of interferon-γ which is quite high compared to patients not status epilepticus seizures. In response to the aftermath of the seizure, Interferon-γ system induces the formation of IL-10 acts as an anti-inflammatory agent that aims to put an end to the action of Interferon-γ. Objective. To know role of Interferon-γ and IL-10 in children with status epilepticus.Methods. This research using cross sectional design with recruiting 30 study sample consisted of 15 children in the seizure group SE and 15 children in the group without SE seizures. Measured levels of IFN-γ and interleukin-10 by ELISA. Results were analyzed with the Mann-Whitney and corelation Spearman to see the relationship levels of IFN-γ and IL-10 in children with status epilepticus with SPSS-23.Results. The results showed significant differences between groups SE and convulsive seizures non SE ;IL10 (p = 0.000) and IFN-γ (p= 000).Conclusion. There are significant correlation between the levels of IFN-γ and IL-10 with status epilepticus.